1975
DOI: 10.1002/cpt1975182205
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of oral dexamethasone

Abstract: Bioavailabilities of dexamethasone tablets and elixir in man were evaluated by each of 3 model-independent methods of pharmacokinetic analysis employing plasma and urinary values as determined by radioimmune assay. There were no significant differences among the results determined by the 3 methods nor between the respective availabilities of the two formulations; the latter averaged 82.6 +/- 17.7% for the elixir formulation and 78.0 +/- 12.1% for tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
1

Year Published

1975
1975
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 0 publications
8
37
1
Order By: Relevance
“…Possibly the use of direct gavage instead of mixture of test substances in the food, might slightly reduce the variability in dose exposure. Systemic exposure of CsA and DEX after oral administration is not confirmed in this study, but oral bioavailability has been shown for DEX [24] and for CsA [25] in humans and pigs respectively. The differences observed in CsA and DEX effects between the various species considered may not only be due to differences in dose and route of exposure, but may also be attributed to differences in the kinetics and metabolism of CsA and DEX in the different species compared.…”
Section: Discussioncontrasting
confidence: 63%
“…Possibly the use of direct gavage instead of mixture of test substances in the food, might slightly reduce the variability in dose exposure. Systemic exposure of CsA and DEX after oral administration is not confirmed in this study, but oral bioavailability has been shown for DEX [24] and for CsA [25] in humans and pigs respectively. The differences observed in CsA and DEX effects between the various species considered may not only be due to differences in dose and route of exposure, but may also be attributed to differences in the kinetics and metabolism of CsA and DEX in the different species compared.…”
Section: Discussioncontrasting
confidence: 63%
“…Complex elimination kinetics of dexamethasone have previously been noted (Duggan et al, 1975). In the present study concurrent administration of cimetidine affected neither AUC nor serum concentrations of dexamethasone showing that there was no apparent effect of cimetidine on dexamethasone elimination.…”
Section: Resultssupporting
confidence: 41%
“…day -1 is given intravenously or orally, plasma concentrations range 40±100 ng . mL -1 [26]. Hence, these in vivo concentrations are covered by the range of concentrations used in the present study.…”
Section: Discussionmentioning
confidence: 97%